TRAINING ON THE USE OF CABRI SOFWARE IN GEOMETRY MATERIALS FOR ELEMENTARY MATHEMATICS TEACHERS IN IDI RAYEUK DISTRICT, EAST ACEH DISTRICT - Fitra Muliani; Amelia Amelia; Fazrina Saumi; Nurviana Nurviana; Ulya Nabilla (LPPM dan PM Universitas Samudra, 2022)
This community service activity aims to provide guidance and training to elementary school teachers regarding the use of mathematical software to deliver geometry-specific material. The targets of this activity were elementary school teachers, namely teachers in the Idi Rayeuk District of East Aceh Regency. The method used in this activity is a direct approach method, lecture or practice. The method of approach is done by observing the problems faced by elementary school teachers, especially in conveying geometry material. The lecture method is carried out through socialization and guidance on difficult material in the field of geometry. While the practice method is done through training in the use of Mathematics software. The results of this activity are the ability of the teacher to guide students in learning the geometry field with the use of Cabri software is adequate, it can be seen from the teacher can already apply the software in delivering the material. In addition, to support this, the PKM Team provided support in the form of modules in order to assist teachers in guiding students.